Costing oral cholera vaccine delivery using a generic oral cholera vaccine delivery planning and costing tool (CholTool). Issue 12 (1st December 2020) - Morgan, Winthrop; Levin, Ann; Hutubessy, Raymond Cw; Mogasale, Vittal
ABSTRACT: Cholera is both an endemic and epidemic disease in many low and middle-income countries (LMICs). Strategies for cholera control include improving water, sanitation, and hygiene; providing early and effective treatment; and deploying oral cholera vaccine (OCV). This last strategy is relatively new, and countries considering its introduction are interested in knowing the potential cost not only of the vaccine, but also the cost of introduction. This paper describes the costing of OCV introduction in LMICs using a publicly available Excel-based tool known as the CholTool. It includes estimates of delivery cost categories which cover not only the service delivery costs (e.g. vaccine procurement, handling, storage, and transport; vaccination administration, monitoring supervision, and field support), but also the programmatic costs associated with introducing a new vaccine (i.e. microplanning, communication and training materials development, sensitization/social mobilization, and personnel training) to ensure that a comprehensive estimate is provided with health payer perspective. CholTool takes the user through a structured sequence of interlinked modules containing input parameter cells (assumptions), decision cells (variable selections), and formulas (calculations) to produce customized cost estimates based on standardized methods. The tool provides both financial and economic cost estimates, to ensure that both costs are available for consideration. Four examples of applications of CholTool are presented in three countries- one in Ethiopia, two in Malawi and one in Nepal. The estimates of economic delivery cost per dose (including service delivery and programmatic costs) were (in USD 2016): 2.89 in Ethiopia, 3.04 in Malawi1, 3.35 in Malawi2 and 3.06 in Nepal. A cost projection conducted before the campaign using the tool and a retrospective costing using the tool in Nepal resulted in no significant difference between economic delivery costs per dose.